Singularity and formation (Bildung) in Schopenhauer as educator of Nietzsche (Educação e Pesquisa, 2009)
Based on Nietzsche's Schopenhauer as Educator, the text seeks to unveil Schopenhauer's model dimension both in the constitution of the ideal of philosopher and thinker that Nietzsche creates to himself, and in the construction of his theory of formation (Bildung). The objective of the article is pursued firstly through the presentation of the critical disposition of the Schopenhauerian thinking and of his refusal to conform to the philosophical and cultural tendencies of his time; then, in a second movement, the text elucidates the specificity of the Nietzschean theory of self-knowledge, and of his concept of singularity, which reveal his theory of the metaphysical ground of nature, leading him to envision the philosopher, the artist, and the saint as the singular types par excellence, in which nature justifies her efforts and goes beyond mere necessity. These typologies reveal the tasks that education, in Nietzsche's view, must engage in if it is to avoid becoming mere abstractionism or noncritical acceptance of the world: to never condescend to cultural fashions; not to separate thinking and life, meaning also that theory and practice go together; to incorporate singularity as that which education promotes; and, lastly, to elect going beyond oneself as the most imperative task in the constitution of the human being in its fullest sense.